Experimental investigation of the effect of graphene nanofluids on heat pipe thermal performance. (5th May 2016) - Sadeghinezhad, Emad; Mehrali, Mohammad; Rosen, Marc A.; Akhiani, Amir Reza; Tahan Latibari, Sara; Mehrali, Mehdi; Metselaar, Hendrik Simon Cornelis
Highlights: The thermal performance of sintered heat pipes is investigated. GNP nanofluid with 0.1wt% concentration exhibits the best performance. The nanofluid causes the formation of a thin film coating on the wick surface. Thermal resistance decreases by up to 48.4%. Graphical Abstract: Abstract: An experimental investigation has been carried out to examine the thermal, performance of a sintered wick heat pipe using aqueous graphene nanoplatelets (GNP) nanofluids. The study focuses on changes in the effects of GNP concentration, heat pipe inclination angle and input heating power. The maximum reduction in the thermal resistance of a sintered wick heat pipe filled with 0.1 wt% of GNP is determined to be 48.4% compared with distilled water (DW). The results show that the maximum effective thermal conductivity enhancements for the heat pipe at a GNP concentration of 0.1 wt% and a tilt angle of 60° for heat input rates of 20, 40, 60 and 80 W are 23.4, 29.8, 37.2 and 28.3%, respectively, compared with a horizontal position ( θ = 0 ° ). It is observed after the experiments that the deposition of GNP creates a coating on the sintered wick surfaces in the evaporator section. This coating layer increases the surface wettability, thereby enhancing the thermal performance of the heat pipe.